The Relationship Between Physical Activity and Nutritional Status During the COVID-19 Pandemic on Students of the Faculty of Medicine Class of 2019, University of Yarsi, Seen from the Perspectives of Medicine and Islam - Prima Alya Trinelza; Sri Wuryanti; Amir Mahmud (Junior Medical Journal, 2022)
Background: With the increasing number of COVID-19 cases that took place quickly and spread in a short time in Indonesia in 2021, the government issued a policy of restricting mobility with the aim of suppressing the spread of COVID-19. The application of online learning policies causes unhealthy lifestyle changes such as reduced physical activity, which will affect the nutritional status of students. The goal of this study was to see if there was a link between FK YARSI students' physical activity and nutritional status during the COVID-19 pandemic. Method: This study used a descriptive analytic study with a cross-sectional research design. The sample is determined by purposive sampling technique and the sample size is obtained through the slovin error tolerance formula of 5% - so that the number of samples in this study is 145 respondents. The data are collected through a questionnaire via google form and are analyzed with Chi-Square Test by using SPSS for windows version 26.0. Results: This study show that most respondents do physical activity in the light category (as many as 127 respondents - 87%) and have normal nutritional status (as many as 92 respondents - 63.4%). Based on the Chi-Square Test, the p value = 0.033, it’s mean significant. Conclution: It can be concluded that there is a significant relationship between physical activity and nutritional status during the pandemic on the '2019 students' of the Faculty of Medicine, Yarsi University.